2020
DOI: 10.1128/aem.00847-20
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Organization of the Stability Module of Broad-Host-Range Plasmid RA3, from the IncU Group

Abstract: The broad-host-range conjugative plasmids have developed diverse adaptive mechanisms defining the range of their promiscuity. The BHR conjugative RA3 plasmid, the archetype of the IncU group, can transfer between, replicate and be maintained in representatives of Alpha-, Beta- and Gammaproteobacteria. Its stability module encompasses ten ORFs apparently organized into five operons, all transcribed in the same direction from several strong promoters that are tightly regulated either by autorepressors or by glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(34 citation statements)
references
References 95 publications
0
34
0
Order By: Relevance
“…6A). It has been also shown that the kfrA operon of RA3 was vital for heterologous plasmid maintenance in E. coli and significantly important in other hosts (18). which was unable to bind to DNA and repress kfrAp.…”
Section: Kfra-dna Binding Is Required For Stable Plasmid Maintenance mentioning
confidence: 99%
See 4 more Smart Citations
“…6A). It has been also shown that the kfrA operon of RA3 was vital for heterologous plasmid maintenance in E. coli and significantly important in other hosts (18). which was unable to bind to DNA and repress kfrAp.…”
Section: Kfra-dna Binding Is Required For Stable Plasmid Maintenance mentioning
confidence: 99%
“…1B ). Recently, we showed that the stability module is organized as a multicistronic operon with at least five differently regulated internal promoters of various strengths ( 18 ). Such an organization may provide, on the one hand, tuned expression of the region when required and, on the other, a species-dependent separation of the particular transcriptional units.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations